BIBLIOMETRIC ANALYSIS OF ARTICLES ABOUT PERIPHERAL VENOUS CATHETERIZATION IN PEDIATRICS - Viviane Reis Fontes da Silva; Isabella Barbosa Meireles; César Cheng; Roberto Carlos Lyra da Silva; Carlos Roberto Lyra da Silva; Luiz Carlos Santiago (Universidade Federal do Paraná, 2019)
Objective: analyze the intellectual production on pediatric peripheral venous catheterization available in the database Scopus. Method: bibliometric study focused on the electronically registered production between 1969 and 2018, using descriptive statistical analysis. Results: 213 articles were retrieved, published in 123 journals. Nursing contributed with 21 (9.8%) articles in the health area. The United States led the ranking with 92 articles (43.1%). The study shows the limitations of the WebQualis journal ranking, showing that 41 (33.36%) journals are not part of any Qualis level. Conclusion: the data elaborated in this study measured the contribution of the scientific knowledge deriving from the publications about catheterization. Therefore, its indicators can be useful for the planning and execution of further studies, and for the scientific community's knowledge on the system it is part of.